Effect of Herbal Medicine, Acupuncture and Moxibustion for Obese Polycystic Ovary Syndrome Patients with Infertility: A Systematic Review and Meta-analysis - Yu-Jin Kim; Ji-Yeon Lee (Journal of Korean Medicine, 2026)
Objectives: This study aimed to evaluate the efficacy and safety of herbal medicine, acupuncture, and moxibustion for infertile women with obesity-associated polycystic ovary syndrome through a systematic review and meta-analysis.Methods: Studies were retrieved from PubMed, CENTRAL, EMBASE, CNKI, OASIS and KISS. RCTs evaluating herbal medicine, acupuncture and moxibustion for obese PCOS patients with infertility were included in the systematic review and meta-analysis. The Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) and Review Manager software version 5.4 were used to assess the risk of bias and to perform the meta-analysis.Results: Twelve studies involving 1,015 participants were included. All studies evaluated herbal medicine, acupuncture, or moxibustion combined with standard therapy. The most common treatment duration was 3 months or three menstrual cycles. Combined treatment significantly improved BMI, HOMA-IR, testosterone, LH, ovulation rate, and pregnancy rate compared with controls, while no significant difference was observed in the miscarriage rate. No significant differences were found in the incidence of mild adverse events or OHSS, whereas LUFS incidence was significantly lower in the combined treatment group.Conclusions: This study investigated the efficacy and safety of herbal medicine, acupuncture and moxibustion in obese PCOS patients with infertility. The findings suggest that combined treatment with herbal medicine, acupuncture and moxibustion provides a significant therapeutic benefit compared with non-combination treatment, without increasing the incidence of adverse events. However, the heterogeneity of the included studies and the limited number of available trials impose restrictions on the generalizability of the findings.